Computer simulation of sunlight concentration due to façade shape: application to the 2013 Death Ray at Fenchurch Street, London. Issue 4 (4th July 2019) - Zhu, Jiajie; Jahn, Wolfram; Rein, Guillermo
Abstract : Reflected sunlight from the Walkie-Talkie building in 20 Fenchurch Street, London, was reported to have caused the melting of plastic components of a car parked at street level in late August of 2013. The incident was explained by the concave-shaped south façade of the building, which converges solar radiation into a hotspot. In this study, we test the sunlight concentation hypothesis with a lighting simulation. A geometry model with material properties was created, and different weather situations were modelled. The results are illustrated in irradiance maps indicating time, position and peak heat fluxes. The highest simulated flux on the day of the incident was 3320 Wm −2 (10 to 15 fold increase compared to direct solar radiation). Additionally, the specific time and day for maximum heat fluxes between June and December were determined . For the worst scenario, which was avoided becuase the sky was partially cover with clouds that day and the hotspot did not fall on street level, the simulations showed that the peak heat flux would have reached well over 4000 Wm −2 .